Autoimmunity in juvenile diabetics and their families. Issue 6131 (15th July 1978) - Bottazzo, G F; Mann, J I; Thorogood, M; Baum, J D; Doniach, D
Abstract : Pancreatic islet cell, thyroid, and gastric antibodies were studied in 116 young insulin-dependent diabetics and 257 relatives. Seventy-four per cent of the diabetics studied within three months of diagnosis had islet-cell antibodies but only 20% of those studied three years or more after diagnosis. Persistence of these antibodies was associated with a high prevalence of thyrogastric autoimmunity, which suggests that some cases have an aetiology similar to that of "polyendocrine" autoimmune disease. Retinopathy or nephropathy, or both, was present in 10 diabetics, who were all members of "autoimmune" families, in which one or more members had organ-specific antibodies. Nine of the 10 healthy relatives with islet-cell antibodies and all families with more than one diabetic were also in this autoimmune group. These data suggest that an autoimmune factor may contribute to juvenile diabetes and that such autoimmune diabetes has a tendency to run in families and may be more likely to cause complications.